2006
DOI: 10.1007/s10535-005-0090-x
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of a chitinase-like protein in embryogenic suspension cultures of Dactylis glomerata L.

Abstract: A chitinase-like 32 kDa acidic protein with a potential chitinase activity has been identified in the medium of embryogenic suspension cultures of Dactylis glomerata L. using an antiserum raised against endochitinase EP3 from Daucus carota L. The presence of this protein discriminates between Dactylis glomerata L. embryogenic and nonembryogenic suspension cultures and thus could be possibly used as a marker for embryogenic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…[45]. Until now, some protein markers for embryogenic potential were described [16,24,25,[46][47][48][49][50][51], as well as a structural marker of embryogenic competency and regeneration ability [52]. Two types of protein markers described in the literature are chitinase and glucanase enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[45]. Until now, some protein markers for embryogenic potential were described [16,24,25,[46][47][48][49][50][51], as well as a structural marker of embryogenic competency and regeneration ability [52]. Two types of protein markers described in the literature are chitinase and glucanase enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Domon et al [57] compared profiles of secreted proteins, which were detected on the surface of preglobulary somatic embryos of four embryogenic cell lines of Pinus caribaea and those, on the contrary to our results, were very similar. This study was based on literature presenting the hypothesis that chitinases are potential markers for embryogenesis, confirmed by differences in extracellular protein profiles among embryogenic cell lines with different embryogenic capacity [17,58] and also between embryogenic and nonembryogenic cell lines [18,[23][24][25]57,[59][60][61]. However, our results showed that in the 18 embryogenic cell lines of P. nigra and the seven cell lines of hybrid firs tested, the presence or absence of any one detected isoform cannot be distinctly associated with the high or low embryogenic potential of the tested cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the presence and role of secreted proteins during somatic embryogenesis in monocots are scarce (6,45,46,47). The results of Borderies et al (6) indicate that AGPs and likely pathogenesis-related proteins and glucanases are involved in the development of maize haploid embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular cysteine proteinase OsCP and cystatin OC-I were found to regulate together cell proliferation in rice suspension cultures (47). Both, an acidic esterase with a putative role in providing a close cell-to-cell contact of different morphological structures during somatic embryogenesis and an endochitinase-like protein secreted only into the medium of Dactylis glomerata L. embryogenic suspension cultures have been proposed as early embryogenic markers (45,46). Recently, a monoclonal antibody MAb3G2 against a cell wall protein (EP48) secreted into the medium by the earliest morphological structures (microclusters) during somatic embryogenesis was selected to monitor the expression of embryogenic potential in D. glomerata L. suspension cultures long before any morphological changes have occurred (44).…”
Section: Introductionmentioning
confidence: 99%